2021
DOI: 10.1038/s41467-021-26098-x
|View full text |Cite
|
Sign up to set email alerts
|

Temporal evolution of master regulator Crp identifies pyrimidines as catabolite modulator factors

Abstract: The evolution of microorganisms often involves changes of unclear relevance, such as transient phenotypes and sequential development of multiple adaptive mutations in hotspot genes. Previously, we showed that ageing colonies of an E. coli mutant unable to produce cAMP when grown on maltose, accumulated mutations in the crp gene (encoding a global transcription factor) and in genes involved in pyrimidine metabolism such as cmk; combined mutations in both crp and cmk enabled fermentation of maltose (which usuall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 56 publications
0
25
0
Order By: Relevance
“…Heterocycles are highly valuable scaffolds for medicinal chemistry, as evidenced by their presence in a majority of biologically active compounds. , More specifically, pyrimidines and quinazolines are frequently featured substructures in drug discovery campaigns and remain popular, appearing, for example, in the recently approved kinase inhibitor Belumosudil and the classic HMG-CoA reductase inhibitor Rosuvastatin (Figure A). …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Heterocycles are highly valuable scaffolds for medicinal chemistry, as evidenced by their presence in a majority of biologically active compounds. , More specifically, pyrimidines and quinazolines are frequently featured substructures in drug discovery campaigns and remain popular, appearing, for example, in the recently approved kinase inhibitor Belumosudil and the classic HMG-CoA reductase inhibitor Rosuvastatin (Figure A). …”
mentioning
confidence: 99%
“… 1 , 2 More specifically, pyrimidines and quinazolines are frequently featured substructures in drug discovery campaigns and remain popular, appearing, for example, in the recently approved kinase inhibitor Belumosudil and the classic HMG-CoA reductase inhibitor Rosuvastatin ( Figure 1 A). 3 10 …”
mentioning
confidence: 99%
“…While the role of curli fibers in AIEC infection has not yet been fully characterised, type 1 fimbriae are considered bona fide AIEC virulence factors that are able to promote bacterial adhesion to epithelial cells [ 18 ]. Interestingly, the expression of both curli fibers- and type 1 pili-encoding genes are negatively regulated in the presence of glucose in LF82, suggesting positive control by the CAP master regulator [ 25 ], whose activity appears to respond also to pyrimidine intracellular concentrations, as recently proposed [ 51 ]. At any rate, the inhibition of pyrimidine biosynthesis appears to have a very extensive impact on AIEC adhesion factors, reiterating its potential as a target for antimicrobial drugs.…”
Section: Discussionmentioning
confidence: 88%
“…Yet, years later it was shown that virtually identical CRP orthologs found in other bacterial species [e.g., Pseudomonas ( Milanesio et al, 2011 )] have nothing whatsoever to do with metabolism but play a role in membrane-related functions. Finally, recent data suggest that in reality CRP in E. coli is not only a promoter-specific regulator but also an authentic genome-scaffolding protein ( Heyde et al, 2021 ) which responds not just to cAMP but to other physiological effectors like cytidine ( Lauritsen et al, 2021 ) and thus has an additional global role. This highlights the importance of maintaining ontologies and the databases relying on them up to date to represent as closely as possible the current state of knowledge.…”
Section: Introductionmentioning
confidence: 99%